Factor Determining Consumers’ Decisions to Purchase Topical Analgesic for Musculoskeletal Disorders in Indonesia - Wahyudi, Aiffian Farhan; Wiedyaningsih, Chairun (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Various choices of topical analgesic to treat musculoskeletal disorders are available on the marketObjectives: This study aims to determine the influence of psychological, cultural, social, and personal factors on purchasing decisions for topical analgesic drugs among consumers who need medication for musculoskeletal disordersMethods: This is cross-sectional quantitative research with an inferential statistics analysis approach. A convenience sampling technique was used to collect data during January 2023 using a questionnaire that was distributed online with a Likert scale via Google Form. A total of 318 respondents from 30 provinces in Indonesia who purchased topical analgesic drugs with complaints of musculoskeletal disorders and aged 18-60 years participated in this study. The data was analyzed using multiple linear regression to determine the relationship of psychological, cultural, social, and personal factors associated with purchasing decisionsResults: The study showed that the majority of respondents were male (50.6%), domiciled in Central Java (20.1%), aged 21-25 years (29.9%), worked as private employees (37.1%) with a working duration of 6-8 hours (59.4%), and had an income of IDR 2,500,000-3,499,000/month (40.6%). The product most frequently purchased was the cream dosage form (60.1%), with locations in pharmacies (74.5%). The results of partial and simultaneous hypothesis testing show that psychological, cultural, social, and personal factors have a significant positive influence (p < 0.05) on the decision to purchase topical analgesic drugs among consumers who need medication for musculoskeletal disordersConclusion: Given that psychological, cultural, social and personal factors influence decisions, it is recommended that marketers understand these factors.